Worship that makes sense to Paul a new approach to the theology and ethics of Paul's cultic metaphors. - Gupta, Nijay K.. (Berlin de Gruyter, 2010)
"This book explores the apostle Paul's temple, priesthood, sacrificial, and worship language with a special interest in how metaphors are powerful vehicles for theological transformation. The methodology of this study combines perspectives from cognitive linguistics, the social-sciences, and rhetorical criticism. In the final synthesis, it is discovered that common factors among Paul's cultic metaphors include an interest in devotion to God, the significance of the body, and the potential for the reshaping of the mind and perception"--P. [4] of cover.
The theology of Paul's cultic metaphors : a history of research -- Methodology and terminology -- 1 Thessalonians and 1 Corinthians -- 2 Corinthians -- Romans -- Philippians -- New life and service to God -- From body of death to temple of life -- Transformed perception -- Metaphor, cult, and identity : exploring coherence -- Conclusion and final reflections.
Based on the author's doctoral thesis
Keywords: Paul, -- the Apostle, Saint; Bible. -- Criticism, interpretation, etc; Atonement -- History of doctrines -- Early church, ca. 30-600; Metaphor in the Bible; Worship -- Biblical teaching; 227 -- Brieven van de apostelen en Paulus--(algemeen)